ANTECEDENT FACTORS AFFECTING REPURCHASE INTENTION ON SHOPEE FOOD - Kezia Christine; Margaret Pink Berlianto (JURNAL MANAJEMEN DAN BISNIS, 2022)
The availability of various e-commerce platforms as shopping media makes it easier for customers to shop conveniently anywhere and anytime. In the context of restaurants, nowadays consumers use an Online Food Delivery System (OFDS) which is an important part of the distribution of the restaurant industry. The competition in the food delivery business is getting fiercer as new entrants emerge. Shopee launched the ShopeeFood food in April 2020. Shopee Food contains a variety of products ranging from food to snacks from various restaurants, as well as Business, Micro, Small and Medium Enterprises (MSMEs) with various discounts and attractive .The urgency of this research is to examine antecedent factors affecting repurchase intention on Shopee Food. This study uses exploratory research design. The number of samples used in this study were 205 respondents live in Jakarta, Depok, Tangerang, and Bekasi who have ordered using Shopee Food. The data analysis method used is Partial Least Square (PLS). The data analysis test tool uses statistical software Smartpls 3.0. This study concludes that some factors affecting the repurchase intention on Shopee Food. Performance expectancy, habit, impulse buying tendency, and orientation to present were found have positive impact on repurchase intention. While, congruity to self image was found has negative impact towards repurchase intention on Shopee Food. In other hand, two other hypotheses which include openess to novelty and alertness to distinction that positively affecting repurchase intention on Shopee Food were rejected.